Enumertion of Enterobacteriaceae in Ice-Based School Children Food in Koto Tangah District, Padang West Sumatera - Bob Refianto; Irdawati Irdawati (Bioscience, 2020)
Elementary students have high playing activities while in school. Hot weather and feeling tired after playing, will cause thirst and to get rid of thirst Elementary school students will buy ice-based snacks. They do not realize, the danger of unhygienic snacks will cause diarrheal diseases, because ice cubes are made by home industries still traditionally without considering hygiene requirements. In some countries, the food industry has moved towards testing Enterobacteriaceae which shows enteric bacterial contamination as a condition hygiene. This study aimed to determine the microbiological hygiene quality of the Enterobacteriaceae numbers in ice-based school children snacks in Koto Tangah Subdistrict, Padang City. This study was a descriptive study. The study was conducted from April to May 2019 at the Laboratory of Microbiology at the Center for Drug and Food Control in Padang. Total samples taken were 20 samples. The results showed that the sample that fulfilled the microbiological quality requirements for sadness was 60% (12 samples) and 40% (8 samples) that did not meet the requirements, the highest results were obtained at SDN 44 Sungai Lareh with a value of 9.82 x 105 colonies/mL.